A NEW LOOK AT THE CLASSIFICATION OF INVENTORIES. - Kempner, Jack J. (The Accounting Review, 1960)
Abstract The article focuses on the classification of inventories in the balance sheets of corporations. A balance sheet is primarily an array of the unexpired costs or a listing of the costs of the assets that have not yet been consumed in the operation of the business. the balance sheet is an attempt to record current or replacement values, the proponents of price level adjustments notwithstanding. This definition of unexpired costs however, applies more specifically to the plant and equipment since these are usually recorded at historical cost and amortized periodically as their usefulness depreciates. There is another combination of assets ordinarily classified as the permanent investments. These assets are not normally consumed in the operation of the business so that no periodic write-off is appropriate. These are usually recorded at historical cost and with the passage of time historical cost varies from its current value. The third major classification, current assets, contains those properties which are already liquid or will be liquidated during the normal operating cycle of the business.